Women and Scotland Literature, culture, politics - Pittin-Hedon, Marie-Odile (Annales littéraires, 2020)
There are outstanding women in the history of Scotland, from Mary Queen of Scots to Nicola Sturgeon. At a time when Scotland is envisaging itself as a nation again, the volume examines the part played by women in this construction. Adopting a perspective that is cultural as well as political, the contributors focus on the representation of historical characters such as Queen Mary and Queen Margaret, Marie de Guise, or women Makars, and on public and cultural policies. The volume also looks at contemporary writing, with authors such as Jackie Kay, Janice Galloway, Ali Smith, Agnes Owens, Morna Pearson or Kathleen Jamie. L'histoire de l'Écosse est jalonnée par l'importance de nombreuses femmes, de Marie Stuart à Nicola Sturgeon.